2010
DOI: 10.1590/s0103-84782010005000033
|View full text |Cite
|
Sign up to set email alerts
|

Florescimento em cana-de-açúcar

Abstract: II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 10 publications
0
9
0
6
Order By: Relevance
“…Each stage has its own environmental and physiological needs. Factors that influence the induction of cane flowering include photoperiod (12-012.5 h of light), temperature (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) C), thermal amplitude (<13 C), latitude (between 10 N and 10 S), and humidity (>60 %), among others [38]. Outside of these conditions, or under adverse conditions, flowering occurs, but often synchrony between male and female lines remains a challenge; therefore, strategies such as sowing at different dates and photoinductive treatments are needed to aid crossbreeding.…”
Section: Seed Productionmentioning
confidence: 99%
“…Each stage has its own environmental and physiological needs. Factors that influence the induction of cane flowering include photoperiod (12-012.5 h of light), temperature (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) C), thermal amplitude (<13 C), latitude (between 10 N and 10 S), and humidity (>60 %), among others [38]. Outside of these conditions, or under adverse conditions, flowering occurs, but often synchrony between male and female lines remains a challenge; therefore, strategies such as sowing at different dates and photoinductive treatments are needed to aid crossbreeding.…”
Section: Seed Productionmentioning
confidence: 99%
“…Houve tendência de aumento dos sólidos solúveis totais ( o Brix) para maiores valores de lâmina de água aplicada, assim como para Pol (%), pureza e ATR (açúcares totais recuperáveis). Quando ocorrem condições favoráveis e a planta atinge uma maturação relativa de desenvolvimento, pode ocorrer o florescimento , que é um fenômeno indesejável em áreas comerciais, devido ao elevado consumo de sacarose e redução do volume de caldo, resultando no aumento do teor de fibras (ARALDI et al, 2010).…”
Section: Introductionunclassified
“…The flowering process occurs simultaneously with the ripening process. Araldi et al (2010) reported that the factors that influence flowering are the sensitivity of the variety to flowering, minimum age of the plant (varieties that are very sensitive to flowering may be induced at six months), photoperiod (optimum is approximately 12.5 hours) and light intensity, temperature (small variations in temperature can cause significant changes in flowering), humidity (humid and cloudy days favor flowering, which is less common in hot, dry regions), altitude (lower altitudes favor flowering), chemical products (various hormonal chemical products decrease flowering, which is of great practical interest) and fertilization (excess nitrogen can hinder or prevent flowering).…”
Section: Wwwintechopencommentioning
confidence: 99%